(untitled) (Texas Journal of Engineering and Technology, 2024)
The article examines the distribution of random voltage change curves and the probability of their occurrence using a probability calculation method, taking into account the randomness of the voltage change at the connection points of electric consumers when evaluating the operating modes of city distribution power networks. Differential and integral histograms of the voltage deviation are given